The effect of dietary seaweed of Caulerpa sp. and Gracilaria sp. on blood glucose levels and histological pancreas of diabetic rats. - Ni Luh Ari Yusasrini; Luh Putu Trisna Darmayanti (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2016)
The aim of this research was to determine the effect of dietary seaweed of Caulerpa sp. and Gracilaria sp. on blood glucose levels and histological pancreas of diabetic rats. A total of 28 male Wistar rats were used in this study. Rats were divided into 4 groups and given different diets i.e. PSN, PSA, PBN and PBS. Bioassay was conducted for 30 days. The analysis conducted on the macronutrient content of the seaweed flour as well as blood glucose levels on day 0, day 1 and day 30 after alloxan injection. At the end of the implementation of  bioassay, animal surgery were performed and pancreas organs were taken for histology observation. The results showed that  Gracilaria sp. and Caulerpa sp. had a crude fiber content respectively 20.48% and 12.47%. Blood glucose levels in all four groups of mice on day 0 ranged from 123.18 mg / dL - 131.96 mg / dL. Feeding PBN and PBS for 30 days lowered blood glucose levels of mice, respectively for 51.63% (from 384.4 mg / dL to 168.52 mg / dL) and 35.24% (from 328.05 mg / dL be 212.42 mg / dL). Histological observation showed that feeding PBN and PBS capable of helping the regeneration of pancreatic cells, thereby feeding both types of seaweed showed hypoglycemic effects in comparison with standard feed.